HAND DEFORMITY IN PARKINSON’S DISEASE: CASE REPORT - Ece Aydoğ; Emel Ekşioğlu; Aytül Çakcı; Özge Yılmaz (Archives of Rheumatology, 2004)
Hand and foot deformities were originally described in Parkinson’s disease in 1864, although its pathogenesis still remains to be clarified. Typical hand deformities are flexion in metacarpopharyngeal joints and hyperextension in interphalangial joints, sometimes accompanied by ulnar deviation. Unlike Rheumatoid arthritis, there is no swelling and stiffness in joints. In this report, a case that was previously misdiagnosed as Rheumatoid arthritis due to deformities in hand and whose Parkinson’s disease was detected upon presentation to our clinic is presented and the differential diagnosis of the disease is discussed.